2004
DOI: 10.1038/sj.eye.6701455
|View full text |Cite
|
Sign up to set email alerts
|

Visual outcomes following ICG assisted ILM peel for Macular Hole

Abstract: Purpose To evaluate the anatomical and visual outcome of indocyanine green (ICG)-assisted internal limiting membrane (ILM) peeling for macular hole surgery. A literature search identified potential factors that may affect the functional success of the procedure. Methods Retrospective case note review of 14 consecutive patients undergoing phacovitrectomy, gas and ICG-assisted ILM peeling for macular hole from July 2001 to July 2002. A 0.5% ICG solution (osmolarity 270 mOsm) was left in contact with the retina f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 15 publications
2
9
3
Order By: Relevance
“…Secondly, the authors used indocyanine green (ICG) as a dye for assisting internal limiting membrane (ILM) peeling in all their patients. While we agree that ICG provides effective staining of the ILM, since 2004 an increasing number of studies have reported the toxic effects of ICG on the retina, which include retinal pigment epithelial changes and optic atrophy (Cheng et al 2005; Posselt et al 2005). We would like to know if the authors have observed any similar toxic effects that may have been induced by ICG in their series of patients.…”
supporting
confidence: 66%
“…Secondly, the authors used indocyanine green (ICG) as a dye for assisting internal limiting membrane (ILM) peeling in all their patients. While we agree that ICG provides effective staining of the ILM, since 2004 an increasing number of studies have reported the toxic effects of ICG on the retina, which include retinal pigment epithelial changes and optic atrophy (Cheng et al 2005; Posselt et al 2005). We would like to know if the authors have observed any similar toxic effects that may have been induced by ICG in their series of patients.…”
supporting
confidence: 66%
“…In situations where the surgeons are uncertain if the ILM was removed in part or completely, it made sense to use ICG. There are, however, serious concerns about the possible toxic effect of ICG 12 13. TB is not specific in that it stains both ERM and ILM.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported our experience with ICG-assisted ILM peel. 2 Our patients achieved a high rate of anatomical hole closure but visual results were disappointing. As a result of these findings we performed an audit of macular hole surgery in our department.…”
Section: Commentmentioning
confidence: 70%